study on effects of repeated salbutamol nebulizations on serum potassium levels and QTc on electrocardiogram in children with acute wheeze - Jain, Gitanjali; Vasnik, Gautam Kumar; Rawat, Ankur (Indian Journal of Child Health, 2018)
Objective: Acute wheeze is a common problem in young children with respiratory disorders. This study emphasizes on whether there are any significant changes in serum potassium levels and QTc interval during repeated salbutamol nebulizations. Methods: A cross-sectional observational study was conducted at a tertiary care teaching hospital. The study group comprised of 41 children in the age group of 6 months–12 years. Pediatric asthma score and vital parameters (heart rate, respiratory rate, and SpO2) were recorded at the onset and end of salbutamol nebulizations. Baseline serum potassium levels were taken at the onset and then at the end. An electrocardiogram (ECG) was taken at 1 h and another at 3 h, for those who continued to require repeated nebulizations until then. Results: The mean fall in serum potassium levels after repeated salbutamol nebulizations was 0.3±0.4 (p<0.05). The mean fall after 3, 4, 5, and 6 salbutamol nebulizations was 0.06, 0.44, 0.66, and 0.43 mEq/L, respectively. There were no significant changes in ECG patterns in these children. The mean QTc at 1 h of repeated salbutamol nebulizations was 0.41±0.02 (s) and that after 3 h (for children requiring repeated nebulizations until then) was 0.43±0.01 (s). The mean rise in QTc at 3 h was 0.004 s, which was not statistically significant (p=0.137). Conclusion: We conclude that serum potassium levels should be monitored in children receiving repeated salbutamol nebulizations for acute wheeze.